Kendala Orang Tua Mendampingi Anak Belajar di Rumah Dalam Menghadapi Situasi Covid 19 - emiyati, ayang (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2020)
In this study thhe writer has the aim to find the obstaclws faced by parents in assisting children to study at home in facing covid 19. The method used in this study is the interview method an uses several reliable sources. The results and discussion in this study the author discussion the impact covid 19 in education, economy and social relations. As well as the authors find the conclusions in this study are as follow: many spend the cost to buy a data package, parents find it difficult because of the lack of material explanation children trust teachers more than their parent, parent experience stress espencially a mother, parent experience stress especially a mother, and the limited facilities available